Missed Opportunities for Prevention of Perinatal Transmission of Hepatitis B: A Retrospective Cohort Study. Issue 10 (2014) - van Schalkwyk, Julie; Nourmoussavi, Melica; Massey, Andrea; Gustafson, Reka; Brodkin, Elizabeth; Petric, Martin; Krajden, Mel; Dobson, Simon; Buxton, Jane; Bigham, Mark; Pick, Neora; Schreiber, Richard; et al.
Abstract : BACKGROUND: Perinatal transmission of hepatitis B virus (HBV) can occur despite postexposure prophylaxis (PEP). Recent literature suggests that antiviral treatment during pregnancy when maternal HBV DNA levels are elevated can further decrease vertical transmission. However, HBV DNA screening is not routinely performed antenatally. OBJECTIVE: To determine the rates of HBV prevalence and perinatal transmission in an antenatal cohort. METHODS: A retrospective review of public health records (December 2008 to December 2010) was performed for both mothers and newborns. RESULTS: A total of 725 mother-infant pairs were included. Of these, 574 of 715 (80%) women had antenatal hepatitis B e antigen (HBeAg) testing performed, and 127 of 574 (22%) were HBeAg positive (HBeAg+). Of babies born to hepatitis B surface antigen-positive (HBsAg+) mothers, only 573 of 725 (79%) received complete PEP. In addition, 172 of 725 (24%) infants did not receive post-PEP blood testing or were lost to follow-up. Of the 552 infants with results available, seven cases (1.3%) of mother-to-child HBV transmission were observed, six of which involved infants born to HBeAg+ women. CONCLUSIONS: Our findings suggest that routine HBeAg screening could identify a subset of mother-infant pairs among HBsAg+ pregnant women who are at higher risk for vertical HBV transmission. Determination of viral load in expectant HBeAg+ mothers may provide more precise insight into HBV transmission to their infants.